Study of Reversible Data Hiding in Encrypted Images - Suryawanshi, Pornima; Mane, Vanita; Padiya, Puja (International Journal of Engineering and Technology, 2018)
In our daily life we outsource the multimedia files such as images, videos etc. to the cloud server.  So this data need to be stored securely. This security is obtained by using different encryption techniques. The study shows that Reserving Room Before Encryption is much better than the Vacating Room After Encryption. Because Reserving Room Before Encryption gives the better image quality and large payload capacity than Vacating Room After Encryption. But RRBE is having some security isues which is limitation of this method. To overcome this problem Reversible Image Transformation (RIT) based framework is used which is client free framework. In this framework the encrypted image is stored in the form of plaintext.  So it will avoid the attention of curious cloud. This paper focuses on different RDH methods.